2020
DOI: 10.2147/ijn.s230949
|View full text |Cite
|
Sign up to set email alerts
|

<p>La<sub>2</sub>O<sub>3</sub> Nanoparticles Induce Reproductive Toxicity Mediated by the Nrf-2/ARE Signaling Pathway in Kunming Mice</p>

Abstract: Purpose: Lanthanum oxide (La 2 O 3 ) nanoparticles (NPs) have been widely used in catalytic and photoelectric applications, but the reproductive toxicity is still unclear. This study evaluated the reproductive toxicity of two different-sized La 2 O 3 particles in the testes. Materials and Methods: Fifty Kunming mice were randomly divided into five groups. Mice were treated with La 2 O 3 NPs by repeated intragastric administration for 90 days (control, nano-sized with 5, 10, 50 mg/kg BW and micro-sized with 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
0
11
1
Order By: Relevance
“…Weight is a key indicator to evaluate the side-effects of drugs. 21 , 37 In vivo studies showed that PSE-NPs had no effect on the bodyweight of mice in the present study. Adriamycin could reduce sperm motility significantly and increase the number of dead sperm in mice.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Weight is a key indicator to evaluate the side-effects of drugs. 21 , 37 In vivo studies showed that PSE-NPs had no effect on the bodyweight of mice in the present study. Adriamycin could reduce sperm motility significantly and increase the number of dead sperm in mice.…”
Section: Discussioncontrasting
confidence: 44%
“…Gene expression levels were calculated as a ratio to the expression of the reference gene, and data were analyzed using the 2 −ΔΔCt method. 21 …”
Section: Methodsmentioning
confidence: 99%
“…Sex hormones are regulated by the hypothalamic–pituitary–gonad (HPG) axis 40 and play a key role in the regulation of the development of the reproductive system and related activities. 41,42 The hypothalamus synthesizes and secretes the gonadotropin-releasing hormone that acts on the pituitary and stimulates the anterior pituitary to release gonadotropins (LH and FSH). FSH regulates sperm production by stimulating the production of Sertoli cytokines, and LH participates in maintaining sperm production through paracrine action, consequently stimulating Leydig cells to produce the androgen testosterone (T) that is extremely important for the development of the male phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those metal‐based NPs mentioned above, other metals and metal oxide nanomaterials could also cause endocrine disorders in aquatic organisms and rat/mouse including Mn 3 O 4 NPs (Zhang et al, 2020), La 2 O 3 NPs (Yuan et al, 2020), CeO 2 NPs (Adebayo et al, 2018; Nedder et al, 2020), Fe 2 O 3 NPs (Sundarraj et al, 2017), Au NPs (Teles et al, 2017) and Au NRs (Jiang et al, 2017), palladium NPs (Leso et al, 2019), Mo NPs (Asadi et al, 2017), CoFe 2 O 4 NPs (Ahmad et al, 2016), and SeNPs ( Table 1). It is worth noting that Se NPs increased serum T at supranutritional level (0.2, 0.4, 0.8 mg/kg) and decreased serum T higher than 4.0 mg Se/kg bw (Liu, He, et al, 2017), which was consistent with the results of another study, 0.5, 1.0, or 2.0 mg/kg nanoselenium treatment can significantly restore the decrease of serum testosterone levels in nickel‐treated rats (Gan et al, 2019), proving that Se NPs has a stimulating effect to T level at low dose.…”
Section: Endocrine Disrupting Effects and Adverse Health Consequences...mentioning
confidence: 99%
“…Cuo NPs did not cause any changes in thyroid hormone levels in fresh water fish under experimental conditions(Canli et al, 2018). Muoth2.1.5 | Other metals and metal oxide nanomaterialsIn addition to those metal-based NPs mentioned above, other metals and metal oxide nanomaterials could also cause endocrine disorders in aquatic organisms and rat/mouse including Mn 3 O 4 NPs(Zhang et al, 2020), La 2 O 3 NPs(Yuan et al, 2020), CeO 2 NPs(Adebayo et al, 2018;…”
mentioning
confidence: 99%